Das vaias à persuasão: movimentos passionais e a tropicália - Wroblewski, Priscilla Harka (2017)
This work is part of the research line "Text and Discourse in Oral and Written Modalities", of the Postgraduate Program in Portuguese Language of the Pontifical Catholic University of São Paulo, has as general objective to analyze the rhetorical constitution of the ethos of the Brazilian composers of the Tropicalia period and the pathos effects in the social. For this to be possible, we reflect on music over time, as well as the ethos interfaces in Brazilian popular music. Based on rhetorical concepts, we analyzed Alegria, Alegria and Domingo at the Park, from 1967, at the III Festival of Brazilian Popular Music, in order to highlight the awakened pathos in the songs. We analyze the constitution of ethos, the use of logos as a resource for a new ideal and the movement of pathos before the songs. We conclude that despite the wrath aroused, the rhetorical elements and the ethos of the speakers were fundamental to the audience's adhesion